Thought, Sound, Silence, Music: "The Turn of the Screw" from Henry James to Benjamin Britten - Llorens Cubedo, Dídac (Complutense Journal of English Studies, 2015)
Although Henry James was always alert to speech and dialogue, his achievement derives largely from the study of human psychology and character, and he is often perceived as a “writer of thought.” The essence of Jamesian style has found an apt correlative in musical discourse and, more specifically, in the language and conventions of opera. James’ The Turn of the Screw evidences an interest in the physical qualities of characters’ speech and recurrently resorts to musical or performative imagery. Silence, however, is at the heart of the novella: Victorian sexual taboo, secrecry shrouding past events, the firstperson narrator’s self-censorship and above all, the soundless presence of the ghostly. Benjamin Britten’s opera adaptation is faithful to James’ text, yet introducing fascinating elements: the definite musical character of the ghosts of Quint and Miss Jessel; their presence on stage frees them from the constraint of the Governess’ narrative filter in the source text; the opera’s focus on Quint, rather than the Governess, sets the homoerotic theme into relief and even suggests the ghost as the origin of the narration.
Keywords: Henry James; Benjamin Britten; The Turn of the Screw; opera adaptation; silence.